2004
DOI: 10.1128/jcm.42.7.3100-3107.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Relatedness of Enterotoxigenic Escherichia coli Strains Isolated from a Cohort of Young Children in Guinea-Bissau

Abstract: In a cohort study of 200 young children in Guinea-Bissau, it was previously found that some enterotoxigenic Escherichia coli (ETEC) strains were more pathogenic than others, depending on the type of toxin that they could produce, and that natural ETEC infections induced substantial protection against new infections with ETEC strains that had the same combination of toxins and colonization factors (CFs). We wanted to describe the clonal relatedness of the ETEC strains isolated during this study and to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 25 publications
5
62
0
Order By: Relevance
“…However, a large US nursery outbreak in 1974-75 was attributed to STproducing ETEC [92] and shortly after, Levine et al [93] demonstrated that strains producing ST alone were capable of eliciting diarrhea, nausea, vomiting and abdominal cramps in adult volunteers. This finding is backed by epidemiological evidence, including controlled studies performed in different parts of Africa, which suggest that ST-producing ETEC are more strongly associated with childhood diarrhea than are LT-producing strains, even though the latter may be more common overall [41,65,91,94]. The same may also be true for travellers' diarrhea [95].…”
Section: Enteropathogenic E Colimentioning
confidence: 85%
See 1 more Smart Citation
“…However, a large US nursery outbreak in 1974-75 was attributed to STproducing ETEC [92] and shortly after, Levine et al [93] demonstrated that strains producing ST alone were capable of eliciting diarrhea, nausea, vomiting and abdominal cramps in adult volunteers. This finding is backed by epidemiological evidence, including controlled studies performed in different parts of Africa, which suggest that ST-producing ETEC are more strongly associated with childhood diarrhea than are LT-producing strains, even though the latter may be more common overall [41,65,91,94]. The same may also be true for travellers' diarrhea [95].…”
Section: Enteropathogenic E Colimentioning
confidence: 85%
“…CFA/IV is typically comprised of CS6 with CS5 or CS4. Steinsland et al [94] sought to determine the role of ETEC in infantile diarrhea and to identify predominant CFAs in Guinea-Bissau.…”
Section: Enteropathogenic E Colimentioning
confidence: 99%
“…They found STp and STh genotypes in 37% (17 of 46) and in 63% (29 of 46), respectively. On the other hand, Steinsland and others 36 in Guinea-Bissau, examined the prevalence of ETEC in young children by PCR detection, reported that only ETEC strains producing STh alone or in combination with LT, but not STp-producing strains, were associated with diarrhea. Identification of ETEC from diarrheic children using PCR or ELISA has not been reported previously from Libya.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the presence of CFAs on the bacterial surface, CFAs may be advantageous as antigenic targets for inducing a prolonged mucosal immune response to ETEC, if incorporated in a vaccine (Girard et al, 2006;Steinsland et al, 2002). Therefore, oral administration of a live ETEC vaccine may be more effective than a killed vaccine, although this is currently debatable.…”
Section: Introductionmentioning
confidence: 99%